2014
DOI: 10.1242/jeb.098426
|View full text |Cite
|
Sign up to set email alerts
|

Level locomotion in wood ants: evidence for grounded running

Abstract: In order to better understand the strategies of locomotion in small insects, we have studied continuous level locomotion of the wood ant species Formica polyctena. We determined the three-dimensional centre of mass kinematics during the gait cycle and recorded the ground reaction forces of single legs utilising a self-developed test site. Our findings show that the animals used the same gait dynamics across a wide speed range without dissolving the tripodal stride pattern. To achieve higher velocities, the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 75 publications
8
73
1
Order By: Relevance
“…If we consider the petiole as the ant's centre of mass (in compliance with Reinhardt and Blickhan, 2014), our results suggest that rearward movements are more wobbly and it can be assumed that the ant has to balance its centre of mass more frequently.…”
Section: Stance-and-swing Envelopesmentioning
confidence: 70%
See 1 more Smart Citation
“…If we consider the petiole as the ant's centre of mass (in compliance with Reinhardt and Blickhan, 2014), our results suggest that rearward movements are more wobbly and it can be assumed that the ant has to balance its centre of mass more frequently.…”
Section: Stance-and-swing Envelopesmentioning
confidence: 70%
“…We measured the x/y coordinates of the tarsal tips with respect to the petiole in the frame before and after a swing phase to quantify the ant's footfall geometry (similar to the work of Mendes et al, 2013 andSeidl andWehner, 2008). We considered the petiole as the centre of mass (Reinhardt and Blickhan, 2014). The measurements were conducted using ImageJ (US National Institutes of Health, Bethesda, MD, USA).…”
Section: Discussionmentioning
confidence: 99%
“…For the smaller ant species L. niger the fundamental frequency is 11.72 Hz with a subharmonic at 2.93 Hz (cf. [23,26]). …”
Section: Deconvolution Of Ants' Walking Signalmentioning
confidence: 99%
“…Results are however based mainly on observations and of qualitative nature (videos, footprints on smoked glass, geometry) and no vibration detection nor an extraction of the excitation signal and its analysis has been conducted. Only recently, Reinhardt and Blickhan [26] studied the locomotion of the wood ant Formica polyctena and showed that the ants used the same gait dynamics across a wide range of speeds without dissolving the tripodal stride pattern in order to perform grounded running. They used a specially designed forced plate setup to measure excitation forces as small as 4 mN with a sensitivity above 50 V/N.…”
mentioning
confidence: 99%
“…For example, a kinematic study on desert ants found that the ground contact durations changed with the inclination of the slope, whereas the positioning of the legs was independent of the slope (Seidl and Wehner, 2008). Other studies have combined kinematics and forces and observed that wood ants and other hexapods such as cockroaches and stick insects pushed with both their front and hind legs for level locomotion (Cruse, 1976;Full et al, 1991;Reinhardt and Blickhan, 2014a), and identified the influence of surface on interactions between ( pre)tarsal structures of weaver ants for level locomotion (Endlein and Federle, 2008). A separate study on vertically climbing weaver ants on a smooth surface found that the legs above the centre of mass (CoM) mainly held their body weight (Endlein and Federle, 2015).…”
Section: Introductionmentioning
confidence: 99%